The Effect of Teach-Back Education on Compliance with Postoperative Wound Care - Erwinsyah; Aguspairi (Journal of Public Health Indonesian, 2026)
Inadequate postoperative wound care is a major cause of surgical complications, including surgical site infections, wound dehiscence, and delayed healing, which leads to increased length of stay, increased costs, and decreased quality of life. Patient adherence to wound care instructions after discharge is strongly influenced by their level of understanding and health literacy, which is often low in the perioperative period. The teach-back method, a communication strategy in which patients are asked to reiterate the information provided in their own words, has been developed as an evidence-based approach to ensure understanding and improve patient adherence. This article aims to examine scientific evidence regarding the effect of teach-back education on postoperative wound care adherence through a narrative literature review of twenty-five articles published between 2021 and 2026, sourced from PubMed, ScienceDirect, and Google Scholar databases. The study results show that the teach-back method consistently improves knowledge, self-efficacy, and adherence to wound care in various surgical populations, from colostomy and orthopedic to cardiac surgery, and is associated with reduced wound complications and hospital readmission rates. It was concluded that teach-back is an effective, simple educational strategy that is feasible to be implemented routinely in perioperative and community nursing practice to improve postoperative wound care outcomes.